2014
DOI: 10.1603/an14003
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering Biology of Egg Parasitoids of Dalbulus maidis (Hemiptera: Cicadellidae) on Perennial Grasses, Volunteer Maize, Stubble, and Drip-Irrigated Maize

Abstract: Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Ciaadellidae) is the most important leafhopper vector of maize plant pathogens in the Americas. However, until now, no study has investigated the overwintering biology of its egg parasitoids. The objective in this study was to find egg parasitoids of D.maidis in perennial grass, volunteer maize, stubble, and drip-irrigated maize habitats in the winter season. Two-week-old D. maidis females were allowed to oviposit on young maize plants for 72 h under laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Emerged (Triapitsyn 2015;Hill et al 2019). Previous studies found a complex of multiple species of egg parasitoids that attack D. maidis on sentinel maize plants in maize crops cultivated in Mexico, Central America, and South America (Virla et al 2009;Moya-Raygoza et al 2012Moya-Raygoza & Becerra-Chiron 2014;Triapitsyn 2015;Luft Albarracin et al 2017). In accordance with the present study, these studies also found A. virlai (which first was identified as Anagrus breviphragma Soyka [Hymenoptera: Mymaridae] and then as A. incarnatus) and Paracentrobia sp.…”
Section: Dalbulus Maidis Eggs Laidsupporting
confidence: 89%
“…Emerged (Triapitsyn 2015;Hill et al 2019). Previous studies found a complex of multiple species of egg parasitoids that attack D. maidis on sentinel maize plants in maize crops cultivated in Mexico, Central America, and South America (Virla et al 2009;Moya-Raygoza et al 2012Moya-Raygoza & Becerra-Chiron 2014;Triapitsyn 2015;Luft Albarracin et al 2017). In accordance with the present study, these studies also found A. virlai (which first was identified as Anagrus breviphragma Soyka [Hymenoptera: Mymaridae] and then as A. incarnatus) and Paracentrobia sp.…”
Section: Dalbulus Maidis Eggs Laidsupporting
confidence: 89%
“…Seasonal maize habitats are very common in tropical America, but little is known about the egg parasitoids that attack corn leafhoppers within maize fields and in their edge zones during the wet (growing) season. It has been previously reported that parasitoids attack the eggs ( Moya-Raygoza and Becerra-Chiron 2014 ), nymphs, and adults ( Becerra-Chiron et al 2017 ) of the corn leafhopper in edge habitats throughout the winter, when the maize crop is absent. In the present study, we found that once maize is planted during the wet season, egg parasitoids attacking D. maidis eggs are most abundant in the maize field and almost absent affecting the abundance of egg parasitoids on the edges, because it is possible that parasitoid species are abundant affecting eggs of another leafhopper species in the edges.…”
Section: Discussionmentioning
confidence: 99%
“…In central Mexico, corn leafhopper adults disperse temporally from November to January to green grasses that inhabit the maize field edges ( Pinedo-Escatel and Moya-Raygoza 2015 ) or move to volunteer maize, uncultivated maize found during winter in several countries of the Americas ( Summers et al 2004 , Carloni et al 2013 , Oliveira et al 2013 ). Edge grasses and volunteer maize are overwinter habitats for D. maidis egg parasitoids such as Mymaridae and Trichogrammatidae species ( Moya-Raygoza and Becerra-Chiron 2014 ).…”
mentioning
confidence: 99%
“…The parasitoid wasps Anagrus columbi Perkins and Anagrus virlai Triapitsyn (both Hymenoptera: Mymaridae) (Triapitsyn 1997) are found abundantly in maize fields (Moya-Raygoza & Becerra-Chiron 2014;. They are solitary and have short life cycles (Meyerdirk & Moratorio 1987;Corbet & Rosenheim 1996), take approximately 17 d to develop, and the average life expectancy of adults is 5 d, whereas few adults survive more than 12 d (Virla 2001).…”
Section: Palabras Claves: Chicharrita Del Maíz; Parasitismo; Hymenopteramentioning
confidence: 99%